Influence of the Digital Mock-Up and Experience on the Ability to Determine the Prosthetically Correct Dental Implant Position during Digital Planning: An In Vitro Study - O'Connor Esteban, Miriam; Riad Deglow, Elena; Zubizarreta Macho, Álvaro; Hernández Montero, Sofía (My University, 2021)
The purpose of this study was to analyze the influence of the digital mock-up and operator experience on the dental implant planning position. A total of 200 dental implants were planned, which were distributed into two study groups: A. dental implant planning by dental surgeons with 5¿10 years of experience (n = 80); and B. dental implant planning by dental surgery students without experience (n = 120). Operators were required to plan eight dental implants in the same maxillary edentulous case uploaded in 3D implant-planning software, before and after using the digital mock-up. Deviations between the dental implant planning positions before and after using the digital mock-up were analyzed at platform, apical and angular levels, and were analyzed using a 3D implant-planning software using Student¿s t test. The paired t-test revealed statistically significant di erences between the deviation levels of participants with 5¿10 years¿ experience and no experience at the platform, apical and angular levels. Digital mock-ups allow for more accurate dental implant planning regardless of the experience of the operator. Nevertheless, they are more useful for operators without dental surgery experience.